2016
DOI: 10.1159/000445654
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms Affect the Effectiveness of Atorvastatin in Treating Ischemic Stroke Patients

Abstract: Background/Aims: The aim of the present study is to investigate whether the single nucleotide polymorphism (SNP) in lipid metabolism related genes would affect the effectiveness of atorvastatin in both Han and Uighur populations. Methods: 200 ischemic stroke patients were treated with atorvastatin. The differences of blood lipid level and their ratios were measured. Six lipid related genes, HMGCR, APOA5, LPL, CETP, LDLR and PCSK9 were selected as candidate genes. And nine SNP loci in these six genes were genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…The 677TT allele was also associated with elevated tHcy levels, predominantly in individuals with low plasma folate levels. Higher tHcy concentrations have in turn been shown to have a negative effect on stroke [16, 19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 677TT allele was also associated with elevated tHcy levels, predominantly in individuals with low plasma folate levels. Higher tHcy concentrations have in turn been shown to have a negative effect on stroke [16, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Functional polymorphisms in the exon region of the MTHFR have been shown to be associated with the pathogenesis of IS. For example, the rs1801133 polymorphism was associated with reductions in MTHFR activity of approximately 70% and 35% in TT and CT genotype carriers, respectively, leading to increased levels of tHcy, which predicted a poor prognosis among IS patients [14-16]. The A1298C variant resulted in substitution of glutamate (Glu) by alanine (Ala) at codon 429 in the S-adenosylmethionine regulatory domain of the MTHFR protein [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, statins have also been reported to have a broad spectrum of biological activities, such as anti-oxidation, anti-inflammation and anti-thrombosis [21-24]. Although studies have demonstrated that statins can reduce intimal hyperplasia and slow atherosclerosis progression via inhibiting VSMCs proliferation and migration [25], the mechanisms behind the favorable effects of atorvastatin calcium on VSMCs are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a primary cause of disability and mortality worldwide [1], and is often treated by intravenous or intra-arterial thrombolysis [2]. Temporary cessation of blood flow to the OGD/R model N2a cells were incubated in glucose-free DMEM and immediately transferred to a humidified atmosphere of 1% O 2 , 94% N 2 , and 5% CO 2 at 37°C for 1 h. Reoxygenation for 12, 24, 48, 72, or 96 h was initiated by rapidly replacing the glucosefree DMEM with normal medium and culturing the cells under normal conditions.…”
Section: Introductionmentioning
confidence: 99%